A obra do poeta politradutor Armand Robin: marcas de uma existência em fuga - Chanut, Maria Emília Pereira [UNESP] (My University, 2013)
Armand Robin was a prodigious translator, that is to say: his works were translated into 22 different languages, not to mention his missing texts. During his bulletin on the radio, it was also possible to notice that 18 idioms were fluently received. This poet was notable not only because of his capacity of knowing several languages, but also because of his conception about translation. According to Robin, the meaning was not enough; a target text (TT) must be based on the recreation of the source text (ST), signification by signification; sound by sound, language by language. Since his first book, Ma Vie sans Moi, was released, Robin always wanted his translated texts were presented as works of his own, creating the idea that there was no difference between ST and TT, before giving priority to translation, either in publications or in radio transmissions. In 1942, ÉditionsGallimard published his single “novel”, Le temps qu’ilfait, which was object of studies related to the poet as a translator, emphasizing the pulse of life, which was visible in his TTs. However, in our paper, we are going to observe his production as an author, more specifically his writings, his novel and some of his fragments, in order to deepen the knowledge about his experience and also understand the dramatic and peculiar speech which is present in his writings.

Armand Robin era um tradutor prodigioso: foram encontrados textos dele traduzidos de pelo menos 22 línguas, sem contar os que desapareceram. Para seu boletim de escutas na rádio, foi possível enumerar 18 línguas fluentemente receptadas. Prodigioso pelo número de línguas, ele também o era por sua concepção da tradução; o sentido não lhe bastava: era necessário recriar o original, sentido por sentido, som por som, língua por língua. Desde a publicação de sua primeira obra, Ma Vie sans Moi, Armand Robin quis que suas traduções fossem apresentadas como obras de sua própria autoria, e mesmo que não se pudesse fazer a diferença entre as duas, antes de dar definitivamente a prioridade às traduções, tanto nas publicações quanto na rádio. Em 1942, a Gallimard publica o seu único “romance” Le temps qu’il fait, O trabalho maior sobre o poeta privilegiou o sujeito tradutor, com ênfase à problemática da pulsão, mais visível nos textos do sujeito tradutor.Neste artigo, privilegiamos a obra do sujeito escritor, e mais especificamente a sua escritura, em seu romance e em seus fragmentos, como forma de aprofundar sua experiência e buscar entender o tão dramático e peculiar discurso presente em sua obra.
The works of the multipurposes poet-translator Armand Robin: marks of a fleeing existence
Keywords: Armand Robin; Poeta-tradutor; Pulsão politradutória; Obra e existência; Poet-translator; Pulse of life; Multipurpose translation; Work and existence